Nursing workload in the emergency room and pediatric ward of a high complexity teaching hospital (Research, Society and Development, 2022)
Objective: To evaluate the Nursing workload of pediatric patients and the predominant type of care in patients admitted to a pediatric emergency room (ER) and a pediatric ward of a high complexity public teaching hospital and its temporal oscillation in the pediatric ER. Methodology: This is an analytical, quantitative, and longitudinal research. The analysis was performed from a secondary database, of a public nature, concerning the Nursing workload demanded by pediatric patients in the years 2013 and 2019. The hospital sectors analyzed were pediatric ER and pediatric ward of a high complexity university hospital in the interior of Minas Gerais state, Brazil. Results: The predominant type of care in both sectors was Intermediate Care. The average Pediatric Patient Classification System score in the pediatric ER was 19.92 and in the pediatric ward was 20.11 points. For the pediatric ER there was no temporal variation in the type of care. The care area of least complexity and that received the highest prevalence of score one was “Support Network” and “Participation of the Accompanying Person” reinforcing the role of the mother or companion in pediatrics. The types of care were dependent on the type of sector studied (p = 0.002) but showed small differences in prevalence. Conclusion: The predominant type of care was Intermediate Care in the pediatric ER and pediatric ward, the profile of each sector interfered with the workload of the nursing team, but no temporal oscillation of the workload was observed in pediatric ER.